Insertion of Intrauterine Contraceptive Device (IUCD) at Caesarean Section after the Delivery of Placenta: An Experience with 60 Cases (Medical Forum Monthly, 2024)
Objectives: To access the safety of Intrauterine Contraceptive Device (IUCD) insertion at Caesarean section after placental delivery. Study design: Observational analytical study of cohort type. Place and duration of study: Department of Obstetrics and Gynecology, Bolan Medical Complex Hospital, Quetta, from September 2009 to August 2010. Patients and Methods: This prospective study was conducted in the department of Obstetrics and Gynecology Quetta from September 2009 to August 2010. Sixty patients who had IUCD inserted at cesarean section were studied and followed for six months. The age ranges from 20-45years. Detailed history of each patient was recorded and thorough physical examination was performed. Patients with findings of any medical disorder were excluded. All analysis and computation including data base were done by SPSS 10. Results: During the study period, a total of sixty women who had IUCD inserted at cesarean section were observed. All the cases were within age group ranging from 20-45 years of age. Out of them 53.3% were between 20 – 30 years, 28% between 31 -40 years, 18.3% belongs to 41-45 years of age. The events that were analyzed during the puerperium were pain, bleeding, infection and expulsion. Considering the postoperative complications, pain was the main complication during the puerperium and it occured in 54% of patients. Endometritis were occurring in 25% of cases and heavy lochia in 21% of cases. The expulsion rate was 8.3%. Conclusion: Women undergoing Cesarean section, who are suitable for using this method, should be given the option of IUCD insertion at the same time.